2020
DOI: 10.1155/2020/4131936
|View full text |Cite
|
Sign up to set email alerts
|

Study on Green Supply Chain Cooperation and Carbon Tax Policy considering Consumer’s Behavior

Abstract: Carbon tax policy has been shown to be an effective incentive for the reduction of carbon emissions, and it also profoundly influences supply chain cooperation. This paper explores the interaction between carbon taxes and green supply chain cooperation. Specifically, we analyze the impact of a carbon tax on green supply chain coordination and further optimize the carbon tax to achieve a win-win situation for both the supply chain and the environment. Because consumer’s behavior has a significant impact on gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…[38] estimated the energy consumption and carbon emissions of 20 mega-cities in China and found that carbon emissions per capita are increasing rapidly by more than 20%, so it is imperative to further control carbon emissions in large cities with the help of high technology. [42] used the life cycle method to carry out relevant calculations on the direct carbon emissions from energy combustion in China. The results showed that in 2017, China's direct carbon emissions from energy consumption increased by more than 300% compared to 1979.…”
Section: Carbon Emissionsmentioning
confidence: 99%
“…[38] estimated the energy consumption and carbon emissions of 20 mega-cities in China and found that carbon emissions per capita are increasing rapidly by more than 20%, so it is imperative to further control carbon emissions in large cities with the help of high technology. [42] used the life cycle method to carry out relevant calculations on the direct carbon emissions from energy combustion in China. The results showed that in 2017, China's direct carbon emissions from energy consumption increased by more than 300% compared to 1979.…”
Section: Carbon Emissionsmentioning
confidence: 99%
“…2.3.2 Effective implementation of carbon tax regulations. It has been proven that there is a strong relationship between sustainable goals of the supply chain and the rate of success of carbon tax regulations (Liu and Hu, 2020). Effective implementation of carbon tax regulations throughout the chain has been realized to be effective for harmful emissions reduction (Hariga et al, 2017).…”
Section: Performance Of Cold Supply Chainmentioning
confidence: 99%
“…ey provide a sensitivity analysis focusing on the effects of variations in the price of the carbon footprint as well as the product recovery rate and show that small increases in the carbon price have little effects on the CLSC network design, but the increase in the recovery rate greatly affects the procurement and recycling processes. Similarly, Liu and Hu [53] investigate the interaction between carbon tax policies and supply chain coordination further including customer behavior. ey use game theory to model the problem.…”
Section: 2mentioning
confidence: 99%